2014
DOI: 10.1002/art.38891
|View full text |Cite
|
Sign up to set email alerts
|

Association of Anti–Acidic Ribosomal Protein P0 and Anti–Galectin 3 Antibodies With the Development of Skin Lesions in Systemic Lupus Erythematosus

Abstract: Objective. The specific autoantibodies and antigens that mediate systemic lupus erythematosus (SLE)-related organ injuries remain largely unknown. This study was undertaken to investigate the antibodymediated immune response that leads to SLE skin lesions.Methods. The study included 85 SLE patients with lupus-specific skin lesions and 31 without skin lesions. The reactivity of serum antibody with skin antigens was determined by immunoblotting using human foreskin as the substrate. Skin antigens were identified… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 46 publications
0
33
0
2
Order By: Relevance
“…Shi et al found that anti‐galectin‐3 antibody of SLE patients was significantly higher as compared to healthy individuals. Additionally, anti‐galectin‐3 antibody decreased with skin recovery and was strongly related to lupus cutaneous vasculitis . It identified the mechanism of SLE skin damage and demonstrated that interaction of tissue antigens with specific antibodies contributes to SLE organ damage.…”
Section: Discussionmentioning
confidence: 96%
See 2 more Smart Citations
“…Shi et al found that anti‐galectin‐3 antibody of SLE patients was significantly higher as compared to healthy individuals. Additionally, anti‐galectin‐3 antibody decreased with skin recovery and was strongly related to lupus cutaneous vasculitis . It identified the mechanism of SLE skin damage and demonstrated that interaction of tissue antigens with specific antibodies contributes to SLE organ damage.…”
Section: Discussionmentioning
confidence: 96%
“…Additionally, anti-galectin-3 antibody decreased with skin recovery and was strongly related to lupus cutaneous vasculitis. 10 It identified the mechanism of SLE skin damage and demonstrated that interaction of tissue antigens with specific antibodies contributes to SLE organ damage. Kang et al showed that serum levels of galectin-3 were elevated in SLE, particularly in those with nephritis, when compared with healthy subjects.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…59,60 Antibodies against 60S acidic ribosomal protein P0 (RPLP0) and galectin 3 are related to the development of skin lesions in SLE. 61 Anti-Ro antibodies have been associated with skin lesions and photo sensitivity, 4 and have been found deposited in the skin of patients with SLE. Ro52 (also known as E3 ubiquitin-protein ligase TRIM21) is a common target of autoantibodies in SLE, and Ro52 is expressed at high levels in the skin of patients with spontan eous CLE and UV-induced inflammatory lesions; indeed, approximately 80% of infiltrating cells within CLE lesions stain positive for Ro52.…”
Section: Inflammatory Cellsmentioning
confidence: 98%
“…Stwierdzono, że hodowle keratynocytów, które nie produkują Gal-3, są bardziej wrażliwe na apoptozę indukowaną przez promieniowanie ultrafioletowe. W 2015 roku ukazała się praca, w której wykazano, że przeciwciała anty-Gal-3 mogą odgrywać istotną rolę w toczniu [33]. Badania przeprowadzono u 85 pacjentów z SLE ze zmianami skórnymi oraz u 31 pacjentów z SLE bez zmian skórnych.…”
Section: Aspekty Dermatologiczneunclassified